RANCANGAN MATERIAL REQUIREMENT PLANNING PADA CLASSIC BISTIK SURABAYA - Christian Janitra Rustandi; Antonius Budhiman Setyawan; Stefanus Budy Widjaja S. (Perpustakaan Universitas Surabaya, 2018)
This study aims to help a small business entity become more productive and efficient. The business entity has a shortage in overcoming the availability of raw materials and time to purchase raw materials. This research uses quantitative approach using Material Requirements Planning method. Data collection is done by using primary data. Primary data in question is by direct observation and interview with the owner and see the place of production. Then the data is processed through data processing that led to various findings of the lack of business entities related to raw material inventory for production. The results of the MRP design that have been made indicate that the improvement of the business entity. Business entities become more efficient, cost-effective and productivity increases.